2019
DOI: 10.1029/2019jg005272
|View full text |Cite
|
Sign up to set email alerts
|

Plant Hydraulic Stress Explained Tree Mortality and Tree Size Explained Beetle Attack in a Mixed Conifer Forest

Abstract: Drought predisposes conifer forests to bark beetle attacks and mortality. Although plant hydraulic stress mechanistically links to tree mortality, its capacity to predict trees' susceptibility to beetle attacks has not been evaluated. Further, both tree size and water supply could influence plant hydraulic stress, but their relative importance remained unknown. In this study, we modeled plant hydraulic stress of individual trees in a mixed forest of Lodgepole pine (Pinus contorta), Engelmann spruce (Picea enge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 97 publications
(156 reference statements)
1
21
0
Order By: Relevance
“…This supported the hypothesis that plants in valleys receive higher water supply and experience less productivity decline when precipitation is low, through lateral flow or soil water storage (Z. Hoylman et al, 2019;Tai et al, 2018Tai et al, , 2019. Areas with higher GPP had higher sensitivity to precipitation (green boxes in Figure 6), consistent with the expectation that greater productivity accumulate and translate into higher biomass, leaf area, and higher water demand and result in faster depletion of water storage during drought (Jump et al, 2017;Tai et al, 2019).…”
Section: Topographic Influence On Ecosystem Sensitivity To Climatic Wsupporting
confidence: 75%
See 2 more Smart Citations
“…This supported the hypothesis that plants in valleys receive higher water supply and experience less productivity decline when precipitation is low, through lateral flow or soil water storage (Z. Hoylman et al, 2019;Tai et al, 2018Tai et al, , 2019. Areas with higher GPP had higher sensitivity to precipitation (green boxes in Figure 6), consistent with the expectation that greater productivity accumulate and translate into higher biomass, leaf area, and higher water demand and result in faster depletion of water storage during drought (Jump et al, 2017;Tai et al, 2019).…”
Section: Topographic Influence On Ecosystem Sensitivity To Climatic Wsupporting
confidence: 75%
“…When sensitivity increased with higher water demand (more positive or less negative β), we expected positive correlations between sensitivity and GPP(green bar in panel e). Tai et al, 2019), resulting in higher sensitivity to precipitation decline (green line in Figure 1c). When there is too much water, increased water supply might further reduce productivity (blue line in Figure 1d), whereas increased water demand might help release the anoxia stress and mediate productivity decline (green line in Figure 1d).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that there is a larger proportion of dead trees among gouged trees, evidencing that gouging by marmosets increases the probability of death of the trees. This can be driven either by mechanical damage to the hydraulic system of the tree, interfering with the water supply (physiological stress), or by increasing the exposure of the tree to potential pathogens (Kautz, Meddens, Hall & Arneth, 2017; Tai et al, 2019). Furthermore, this effect is larger on smaller trees.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that there is a larger proportion of dead trees among gouged trees, indicating that gouging by marmosets increases the probability of tree mortality. This could be driven either by mechanical damage to the hydraulic system of the tree, interfering with the water supply (physiological stress), or by increasing the exposure of the tree to pathogens (Kautz, Meddens, Hall, & Arneth, 2017; Tai et al., 2019). Furthermore, mortality is higher for small trees.…”
Section: Introductionmentioning
confidence: 99%